Application of taguchi method in the optimization of reacttive mobile ad hoc networks routing procotols parameters - Abdullah, Muhammad Hisyam Lee (Penerbit UTM, 2006)
A Mobile Ad-Hoc Network (MANET) is a collection of wireless nodes forming a temporary network without the aid of any established infrastructure or centralized administration [2]. Establishing a route from a source node to a destination node is a fundamental problem in MANETs. In general, routes between nodes in MANET may include multiple hops. Each node will able to communicate directly with any other node that resides within its transmission range. For communicating with nodes that resides beyond this range, the node needs to use intermediate nodes to relay the messages hop by hop. Routing protocols play a significant role in this kind of network by selecting the route to forward the packets and in establishing a connection